Fabrication of hybrid electric chopper tyre motorcycle front suspension - Muhammad Amir Akmal, Ahamad Khalid (2013)
This thesis discussed the process of fabricating of hybrid electric chopper type motorcycle front suspension system. Firstly, the current chopper type motorcycle and hybrid system are studied. The studies include the design, advantages, disadvantages, material and installation. Later, the concept is selected for further studies which involving three dimensional modeling by using software SolidWorks. The fabrication of this hybrid electric chopper type motorcycle front suspension system is later do because the chassis first. The found out of problems also included. The problems covered from the start till project ends. Lastly, the conclusion of the project is documented and given some recommendation for further studies on the project.